Efektivitas E-Booklet Gizi dalam Meningkatkan Pengetahuan dan Sikap Remaja Putri tentang Anemia - Nadiah Salwa Mulyani; Astidio Noviardhi; Kun Aristiati Susiloretni (JURNAL RISET GIZI, 2025)
Background: Anaemia is a common health problem among adolescents and can affect academic performance. In 2023, the WHO reported that the prevalence of anaemia among adolescent girls was 48.9%, up from 37.1% in 2018. The SKI study in 2023 recorded a national prevalence of 16.2%, while in Central Java and the city of Semarang, the prevalence was around 30%. These high figures highlight the importance of providing effective nutrition education to improve adolescent girls' knowledge and attitudes towards anaemia, including through e-booklets. Objective: To analyze the effectiveness of e-booklet nutrition education on knowledge and attitudes about anemia among adolescent girls. Method: This study was a quasi-experimental study with a pretest-posttest control group design. Twenty respondents were included in each group. The data collected were knowledge and attitude scores obtained through a questionnaire. Statistical analysis used the Independent T-Test and the Mann-Whitney test. Results: E-booklets are considered a suitable educational medium. The treatment group demonstrated greater increases in knowledge (22) and attitude (12.90) than the control group, which increased by 11 and 7.90, respectively. Using e-booklets for education had a significant effect on the knowledge (p = 0.000) and attitude (p = 0.002) of adolescent girls. Conclusion: The e-booklet on anemia nutrition education effectively increased knowledge by 90% and attitudes by 88%.